Comparative efficacy of clopidogrel-aspirin combination therapy versus aspirin monotherapy in preventing recurrent events in transient ischemic attack and minor stroke: a systematic review and meta-analysis - Ahmad Mujtaba Bhutto; Rana Ali Raza; Mohammad Bilal Abbasi; Iman Jauhar; Naeemullah Arbani; Muhammad Mubashir; Abdul Raheem; Taha Basit Ameen; Syed Muhammad Sinaan Ali (The Egyptian Journal of Internal Medicine)
Abstract Background and objective Stroke is a leading cause of disability and death globally. Dual antiplatelet therapy (DAPT) with clopidogrel and aspirin is a common intervention for acute ischemic stroke (AIS) and transient ischemic attack (TIA). This meta-analysis aims to evaluate the efficacy and safety of DAPT compared to aspirin monotherapy in preventing recurrent stroke. Methods We performed a systematic search of electronic databases including PubMed, MEDLINE, Embase, and Scopus up to April 1, 2024. Eligible studies involved adult patients with acute stroke or TIA receiving either DAPT with clopidogrel and aspirin or aspirin monotherapy, with follow-up durations between 30 and 90 days. Data were extracted on recurrent stroke, hemorrhagic stroke, myocardial infarction, all-cause mortality, and functional outcomes measured by the modified Rankin Scale (mRS). Statistical analyses were conducted using relative risk (RR) and odds ratio (OR) with 95% confidence intervals, and heterogeneity was evaluated using I 2 statistics. Results From 2344 articles screened, 33 studies involving 15,376 participants were included. DAPT significantly reduced the risk of recurrent stroke (RR 0.85, 95% CI 0.75–0.97, I 2 = 42%, p = 0.02). However, DAPT was associated with an increased, but not statistically significant, risk of hemorrhagic stroke (RR 1.27, 95% CI 0.55–2.90, I 2 = 51%, p = 0.23). There were no significant differences in the risk of myocardial infarction or all-cause mortality between the two groups. Functional outcomes indicated that DAPT reduced the risk of disability (OR 0.80, 95% CI 0.70–0.92, I 2 = 35%, p = 0.004). Conclusion DAPT with clopidogrel and aspirin is more effective than aspirin monotherapy in reducing recurrent strokes but may increase the risk of hemorrhagic stroke. Individualized patient assessment is crucial to balance the benefits and risks of DAPT. Further high-quality, long-term studies are needed to confirm these findings and inform clinical practice.